THE CONCEPT OF MARKETING AUDIT: PROBLEMS OF THEORY AND PRACTICE - Holyash, Iryna; Halushka, Natalya (Journal of European Economy, 2017)
The development of market relations in Ukraine calls forth the questions of strengthening the competitive capacity of enterprises on the market and their timely adaptation to changes in competitive marketing environment, recognition of an urgent need for practical application of the principles of marketing audit for evaluation of enterprise's production and sales operations, as well as revealing the problems and hidden potential in the way of reaching operational and strategic goals and achieving the desired result. The formation of marketing audit is one of the most complicated tasks of strategic management. Its necessity is preconditioned by the incoming information describing the financial and economic activity of an enterprise, by the elements of company's business environment, and on this basis by the coordination of the management system operation for achieving the set goals.